EFISIENSI SERAPAN P TANAMAN KENTANG PADA TANAH ANDISOL DENGAN PENAMBAHAN VERMIKOMPOS - Hery Widijanto; Jauhari Syamsiyah; Betta Dwi Isti Ferela (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2008)
Title : Efficiency of P Uptake by Potato in Andisols by Vermicompost Addition. Mostly potatoes (Solanum tuberosum L.) are planted on Andisols that have problem in phosphate fixation. The aim of this research were to know the efficiency of P fertilizing in Andisols that were added vermicompost and SP36 and to know potatoes yield in Andisol. This research was conducted at Tawangmangu, Karanganyar on October until December 2007. The method used was split plot design, as a main plot was vermicompost, i.e. no vermicompost and 10 ton.ha-1 vermicompost. Sub plot consist of four levels of P fertilizer (SP36), i.e. 100, 250, 400, 550 kg.ha-1 and control. The observation variables are available P, efficiency of P absorption, weight and diameter percentage of potato tuber. F test, Kruskal-Wallis test, and DMRT 5% test is used to analysis data. The result of this research shows that there is interaction betwen vermicompost and 400 kg.ha-1 doses SP36 to highest available P in the soil is 2.157 ppm P2O5, but there is no interaction on yield. The addition of 10 ton.ha-1 vermicompost can increase weight of potato tuber (30.83 %) and decreased percentage of potato tuber amount diameter in < 9 cm (48.05 %). Addition of 250 kg.ha-1 SP36 can increase percentage of potato tuber amount diameter in 12-15 cm (57.46%). The highest result of potato is reached on tuber diameter > 15 cm (37.16%) with 10 tons.ha-1 vermicompost additions. Keywords: vermicompost, P fertilizer, potato, Andisols